Social economic costs of type 1 diabetes mellitus in pediatric patients in Spain: CHRYSTAL observational study. (May 2017) - López-Bastida, Julio; López-Siguero, Juan Pedro; Oliva-Moreno, Juan; Perez-Nieves, Magaly; Villoro, Renata; Dilla, Tatiana; Merino, María; Jiang, Dingfeng; Aranda-Reneo, Isaac; Reviriego, Jesús; Vázquez, Luis Alberto
Highlights: This is the first estimation of informal care costs of children with T1DM. HbA1c < 7.5% level is associated with significantly lower costs than HbA1c ≥ 7.5%. Absence of T1DM related complications leads to significantly lower costs. Informal care time is the largest cost associated with T1DM in children. Abstract: Aims: To estimate the social-economic costs of Type 1 Diabetes Mellitus (T1DM) in patients aged 0–17 years in Spain from a social perspective. Methods: We conducted a cross-sectional observational study in 2014 of 275 T1DM pediatric outpatients distributed across 12 public health centers in Spain. Data on demographic and clinical characteristics, healthcare utilization and informal care were collected from medical records and questionnaires completed by clinicians and patients' caregivers. Results: A valid sample of 249 individuals was analyzed. The average annual cost for a T1DM patient was €27, 274. Direct healthcare costs were €4070 and direct non-healthcare cost were €23, 204. Informal (familial) care represented 83% of total cost, followed by medical material (8%), outpatient and primary care visits (3.1%) and insulin (2.1%). Direct healthcare cost per patient statistically differed by glycated haemoglobin (HbA1c) level [mean cost €4704 in HbA1c ≥7.5% (≥58 mmol/mol) group vs. €3616 in HbA1c < 7.5% (<58 mmol/mol) group)]; and by the presence or absence of complications and comorbidities (mean cost €5713 in group with complications or comorbidities vs. €3636 in group without complications or comorbidities). Conclusions: T1DM amongst pediatric patients incurs in considerable societal costs. Informal care represents the largest cost category.